STRATEGI PENGEMBANGAN AGRIBISNIS PEMBIBITAN ALPUKAT (Persea americana) DI KELURAHAN SUKAHATI KECAMATAN CIBINONG KABUPATEN BOGOR - Sindy Adreina; Arti Yoesdiarti; Apendi Arsyad (JURNAL AGRIBISAINS, 2022)
This study aims to determine the feasibility of avocado seed agribusiness farming and develop a strategy for developing avocado seed agribusiness in Sukahati Village, Cibinong District, Bogor Regency. Respondents for farming analysis are 20 and were selected using simple random sampling. The selection of respondents for strategy formulation used purposively, namely 13 experts. The analysis was used is descriptive analysis, farming feasibility analysis and SWOT analysis. Farming analysis on a land area of ​​3,138 m2 for 6 months shows that this business is feasible with a profit of Rp.343,841,358, - and an R/C value of 6.95. Environmental analysis through the IFE and EFE matrices obtained a weighted score of 2.87 on internal factors and 2.85 on external factors so that the position in the Internal External matrix is ​​in cell V (five) with Growth Strategy. The SWOT analysis resulted in 14 strategic steps: (1) Intensifying marketing through social media accounts with soft selling, (2) utilizing government facilities, (3) training to improve seed quality, (4) Creating demonstration plots and exhibitions to attract public interest, (5 ) Cooperation between farmers to meet consumer needs, (6) provide each other with avocado seed needs and information, (7) help each other convey information on farming techniques, (8) maximize strategic locations to capture markets, (9) Utilize training to improve institutional development, management finance, cultivation technology and marketing, (10) take advantage of government support for business development, (11) Conduct online meeting activities if time and distance are constrained, (12) Maximize the benefits of Network Culture, (13) often hold discussions on farming techniques, share market, and absorption of market information, (14) strengthen location branding and product quality by utilizing promotion media.